Civil Law and Social Inequality: A Politics of Legal Protection Perspective - Shohib Muslim (PT. Anagata Sembagi Education, 2025)
Civil law is normatively constructed on the assumption of formal equality among legal subjects. In social reality, however, civil law relations frequently operate within conditions of structural inequality arising from disparities in economic power, access to information, and bargaining position. The state responds to such inequalities through regulatory interventions framed as legal protection. This article examines the role of civil law in addressing social inequality from a legal protection politics perspective. Employing normative legal research with statute, conceptual, and case approaches, this study identifies normative ambiguity in civil law concerning the criteria for identifying protected weak parties, the boundary between legal protection and restrictions on private autonomy, and inconsistencies between the Civil Code and social-economic protection legislation. The findings demonstrate that such ambiguity renders civil law protection selective and often ineffective in correcting social inequality. This article argues for a normative reconstruction that positions civil law as a constitutional instrument for correcting social inequality, treating private autonomy as a conditional principle subject to substantive and distributive justice considerations.